GNSS multipath mitigation in direct position estimation: algorithm design and implementation strategies - Jia, Qiongqiong; Wu, Renbiao (GPS solutions, 2025)
Direct Position Estimation (DPE) allows for the direct estimation of the GNSS receiver’s position, velocity, and timing (PVT) within the navigation domain by jointly utilizing data from all satellites at the sample level, thereby bypassing the intermediate step of computing observables. This paper aims to mitigate the PVT bias induced by multipath in DPE. To achieve this, we proposed a RELAXation-based algorithm called RELAX-DPE. The core idea of the RELAX-DPE algorithm is to purify the multipath-contaminated combined correlation diagrams in the navigation domain by estimating the parameters of the received signals, where the parameters of the line-of-sight (LOS) and the reflected ones are estimated in an iterative manner. Furthermore, we present an efficient implementation of the RELAX-DPE algorithm on a soft-ware defined receiver (SDR). In this implementation, grid-based DPE navigation solving is utilized, and the combined correlation diagram in the navigation domain is calculated using a batch pre-correlation method during each iteration of the parameter estimation process. To validate the effectiveness of the proposed RELAX-DPE algorithm, we conducted experiments based on semi-analytic simulations and simulated data sets. The results indicate that the performance of RELAX-DPE is influenced by the navigation domain grid range and grid resolution, particularly when the carrier-to-noise ratios (CNRs) are low and the relative code delay of multipath is large. A grid range of ± 200 m and a grid resolution of about 10 m are confirmed as appropriate selections. Simulation results from the SDR across various multipath scenarios further confirm the efficacy of the RELAX-DPE.